The Effect of Principal Managerial Competence and Work Climate on Teacher : Performance Pengaruh Kompetensi Manajerial Kepala Sekolah dan Iklim Kerja terhadap Kinerja Guru - Munfa’ati, Izzatul; Haryanto, Budi (Indonesian Journal of Innovation Studies, 2026)
General Background: Teacher performance is related to professional task implementation, including planning, teaching, assessment, communication, and innovation. Specific Background: At SDI Cahaya Islami Candi–Sidoarjo, principal managerial competence and work climate are examined in relation to teacher performance. Knowledge Gap: Previous studies have examined managerial competence and work climate in relation to teacher performance, while this study focuses on comparing their respective contributions and their simultaneous relationship with teacher performance. Aims: This study examines principal managerial competence and work climate in relation to teacher performance. Results: Using a quantitative quasi-experimental design with 36 teachers, questionnaire data were analyzed using SPSS 30.0. Managerial competence recorded a mean score of 65.42, while work climate recorded 57.89. The simultaneous test showed F = 24.915 and sig. = 0.001. Novelty: Managerial competence showed a higher mean score than work climate. Implications: Strong managerial competence and a supportive work climate are important considerations for teacher performance. Key Findings Highlights Managerial competence recorded the higher mean score of 65.42. Work climate recorded a positive mean score of 57.89. Both variables were jointly significant with F = 24.915 and sig. = 0.001. Keywords : Principal Managerial Competence, Work Climate, Teacher Performance, School Leadership, Elementary School